1990
DOI: 10.1002/clc.4960130510
|View full text |Cite
|
Sign up to set email alerts
|

External compression by metastatic squamous cell carcinoma: A rare cause of left main coronary artery narrowing

Abstract: Summary: A 69-year-old male with carcinoma of the lung developed unstable angina pectoris during his last few months of life. At necropys, the coronary arteries were free of atherosclerotic plaque, but the left main artery was severely narrowed by external compression from neoplastic metastases. Persistent anterior ST-segment elevation without evolutionary changes of myocardial infarction was a clue to cardiac involvement by tumor. Direct and indirect effects of metastatic tumors upon the coronary arteries inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
15
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…In patients with lung carcinoma, coronary tumor embolism is theoretically facilitated by the fact that direct embolism from pulmonary veins via the left heart in the coronary arteries is possible. True coronary tumor thromboembolism as the cause of fatal ischemic heart disease, as demonstrated in this case report, in patients with malignant tumors must be differentiated from myocardial infarction because of external compression of large coronary arteries by infiltrative tumor [5]. Another possible cause of myocardial infarction in patients with malignant tumors is a disturbed balance between pro-and anticoagulative processes in the blood, which may eventually lead to conventional coronary thrombosis.…”
Section: Discussionmentioning
confidence: 80%
“…In patients with lung carcinoma, coronary tumor embolism is theoretically facilitated by the fact that direct embolism from pulmonary veins via the left heart in the coronary arteries is possible. True coronary tumor thromboembolism as the cause of fatal ischemic heart disease, as demonstrated in this case report, in patients with malignant tumors must be differentiated from myocardial infarction because of external compression of large coronary arteries by infiltrative tumor [5]. Another possible cause of myocardial infarction in patients with malignant tumors is a disturbed balance between pro-and anticoagulative processes in the blood, which may eventually lead to conventional coronary thrombosis.…”
Section: Discussionmentioning
confidence: 80%
“…[5][6][7][8][9] One case report describes a tumor that caused extrinsic compression of an epicardial vessel, which led to myocardial damage. 10 Here, we report an apparently unique case of malignancy that caused STE-by direct apposition of a lung mass on the myocardium without any evidence of cardiac metastases, coronary artery invasion or compression, or pericardial involvement. The persistent current of injury detected on ECG is thought to have occurred from direct myocardial compression.…”
Section: Discussionmentioning
confidence: 93%
“…Extrinsic compression of coronary artery by mediastinal mass resulting in significant coronary artery narrowing is very rare, and only a few cases were previously described [3,4]. Weinberg et al [3] described a case of left main coronary artery narrowing caused by the extrinsic compression of lung cancer, and Zeymer et al [4] also reported similar case caused by mediastinal lymphoma.…”
mentioning
confidence: 95%
“…Extrinsic compression of coronary artery by mediastinal mass resulting in significant coronary artery narrowing is very rare, and only a few cases were previously described [3,4]. Weinberg et al [3] described a case of left main coronary artery narrowing caused by the extrinsic compression of lung cancer, and Zeymer et al [4] also reported similar case caused by mediastinal lymphoma. Direct invasion and encasement of coronary artery by metastatic tumors was the cause of coronary artery narrowing in these cases, but the simple extrinsic compression of coronary artery by a non-metastatic large mediastinal mass was the cause of significant RCA stenosis in the present case.…”
mentioning
confidence: 95%